The Traumatized Vertebral Spine Reloaded: Injury Mechanisms and their Radiologic Patterns - Schueller, Gerd; Schueller-Weidekamm, Claudia (Seminars in Musculoskeletal Radiology, 2014)
The ideal classification of spinal trauma does not yet exist, primarily because the implementation of morphological, biomechanical, and clinical parameters in a single nomenclature is a difficult task. For radiologists and surgeons, who are partners in trauma teams, only a few classifications of injury patterns have been shown to be useful enough to provide rapid and stable therapy decisions in daily practice. From a didactic point of view, however, simplifications of injury mechanisms are of help to become aware of the most important radiologic injury patterns of vertebral trauma. The members of trauma teams should be aware of the strengths and limitations of existing descriptions of imaging features when reporting trauma to the spine. These are discussed in this article.
Keywords: trauma; spine; injury; diagnosis; CT; MRI